UHF meander bowtie antenna for RFID application - Norsaidah Muhamad Nadzir; M.K.A. Rahim; F. Zubir; H.A. Majid (IAES Indonesian Section, 2019)
This paper describes the development of four different ultra-high frequency (UHF) radio frequency identification (RFID) tag antenna using polycarbonate material or transparent paper as the substrate and aluminum tape as the radiating element. The main advantage of the method is that the materials are easy to obtain where it can be found in any hardware stores or in any general online shop. Plus, the antennas are designed in such a way that a meander line is traced along the shape of a bowtie antenna so that the antenna would operate at UHF band. The results of all four of the tag antenna designs are discussed and compared using graph obtained from Computer Simulation Technology (CST) simulation results and measurement results obtained from a portable Vector Network Analyzer (VNA) for the reflection coefficient, S11, and measurement results taken from VNA in chamber room for the radiation pattern. Finally, the results show that the measured results are in agreement with the simulated result and that the UHF RFID tag antennas are able to operate at UHF RFID band.